(untitled) (Journal of actual problems of jurisprudence, 2022)
The research topic is aimed at analyzing the legislation of the Republic of Kazakhstan on the formation and implementation of information policy. The purpose of the article is to analyze the concept and content of the term "information policy", as well as the presence of this concept in the normative acts regulating the issues of domestic and foreign policy of Kazakhstan. The aim is also to analyze the problems caused by insufficient attention to the issues of modern information policy as an important component of national security. The scientific and practical significance of the article lies in the fact that it substantiates the need to develop and implement the concept of information policy of Kazakhstan, where special attention should be paid to the issues of interaction between state bodies and the population of Kazakhstan in the conditions of military and emergency. The research methods used were the method of systematic analysis of regulatory legal acts of Kazakhstan, as well as the method of comparative analysis of legislation and practice of Kazakhstan with issues of domestic and foreign policy of other countries. The results of the study should include a recommendation on the need to develop a conceptual document on the information impact and interaction of the state with citizens in order to ensure the protection of the national interests of the country. Keywords: information policy; state information policy, national security, public administration.